2023
DOI: 10.1021/acs.accounts.3c00543
|View full text |Cite
|
Sign up to set email alerts
|

Inner- and Outer-Sphere Cross-Coupling of High Fsp3 Fragments

Simona Kotesova,
Ryan A. Shenvi

Abstract: Metrics & MoreArticle Recommendations CONSPECTUS: Natural product research originates from a desire to explore, understand, and perturb biological function with atomic precision. To reach these goals at all, let alone efficiently, requires thoughtful and creative problem solving. Often this means bold disconnections that would simplify access to complex structures, if only the methods existed to bridge these theoretical gaps. Whereas biological interrogations provide long-term intellectual value and impetus, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…A simple and predictable method to form quaternary C’s akin to classic N quaternization would be an appealing transformation. Our previous studies have demonstrated how radical methods can be leveraged to cross-couple olefins with other olefins or alkyl/aryl halides ( 6 , 7 ). In many cases, quaternary C synthesis can be achieved through such methods.…”
mentioning
confidence: 99%
“…A simple and predictable method to form quaternary C’s akin to classic N quaternization would be an appealing transformation. Our previous studies have demonstrated how radical methods can be leveraged to cross-couple olefins with other olefins or alkyl/aryl halides ( 6 , 7 ). In many cases, quaternary C synthesis can be achieved through such methods.…”
mentioning
confidence: 99%
“…Both of these stoichiometric reactions have now given way to catalytic variants with higher chemoselectivity and broader functional group tolerance. Particularly important examples involve Markovnikov-selective hydrofunctionalizations that form quaternary carbons via merger of complex, high F sp 3 fragments . Such fragment couplings form the backdrop to this short Synopsis.…”
mentioning
confidence: 99%